2021
DOI: 10.1074/jbc.ra120.016352
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and mechanism of GPCR proton sensing

Abstract: Of the 800 G protein–coupled receptors (GPCRs) in humans, only three (GPR4, GPR65, and GPR68) regulate signaling in acidified microenvironments by sensing protons (H + ). How these receptors have uniquely obtained this ability is unknown. Here, we show these receptors evolved the capability to sense H + signals by acquiring buried acidic residues. Using our informatics platform pHinder, we identified a triad of buried acidic residues shared by all three receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 56 publications
(103 reference statements)
6
49
0
Order By: Relevance
“…Furthermore, as reported in Fig. 5E, these pH titrations confirmed that the adenosine receptor A2a (ADORA2A) is activated by acidic pH in a manner strikingly similar to the known acid-activated proton sensor GPR68 (8). Furthermore, these pH profiles established that ADORA2A senses protons through the G i/o , G q , and G 12/13 families of Gα subunits but did not indicate proton-sensing through the canonical ADORA2A Gα subunit G α,s .…”
Section: Significancesupporting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, as reported in Fig. 5E, these pH titrations confirmed that the adenosine receptor A2a (ADORA2A) is activated by acidic pH in a manner strikingly similar to the known acid-activated proton sensor GPR68 (8). Furthermore, these pH profiles established that ADORA2A senses protons through the G i/o , G q , and G 12/13 families of Gα subunits but did not indicate proton-sensing through the canonical ADORA2A Gα subunit G α,s .…”
Section: Significancesupporting
confidence: 74%
“…As shown in Fig. 1D, we previously engineered a high-throughput platform for studying human GPCRs that uses the isolated Ste2 pathway: Dynamic Cyan Induction by Functional Integrated Receptors, DCyFIR (8,17,18,21). In the DCyFIR platform, a human GPCR is coupled to a MAP kinase signaling cascade via a human/ yeast C-terminal Gα chimera in which the last five residues of the native yeast Gα subunit, Gpa1, are replaced with the last five residues of a human Gα (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the G2A receptor seems to be less sensitive to pH changes than the other three members of the proton-sensing GPCR family, probably due to the lack of crucial histidines at the respective positions [8]. Moreover, a recent publication suggested a triad of acidic amino acids for proton detection that are conserved in GPR4, OGR1, and TDAG8, but not in G2A, which may additionally explain the weak proton activation of G2A, and which provides molecular evidence for the evolution of protonsensing GPCRs allowing phylogenetic classification of the receptors [15].…”
Section: Proton-sensing Gpcrs-structural Features and Physiologymentioning
confidence: 97%